GAMBARAN PENGETAHUAN FAD DIET, GIZI SEIMBANG DAN PERSEPSI BODY IMAGE PADA REMAJA PUTRI DI SMA NEGERI, BANDYUNG (Jurnal Kesehatan Siliwangi, 2022)
eenagers often judge their body shape and want to have a body shape like other people, so they go on a strict diet which is not necessarily safe. Fad Diet is a diet that promises very fast weight loss but does not consider side effects. The purpose of this study was to study the description of knowledge of fad diet, balanced nutrition, and perception of body image in adolescent girls at SMA Negeri 2 Majalaya, Bandung Regency. The research design used was cross sectional. The population of this study were all students of class XI majoring in science at SMA Negeri 1 Majalaya. The total sample is 90 people. Data collection includes general data, anthropometry, fad diet knowledge, balanced nutrition knowledge, and body image perception. Data was collected using a google form which was sent through the whatsapp group media. The results showed that the description of fad diet knowledge did not significantly affect the perception of body image. It is shown that the sample who has sufficient and good knowledge still has a dominant negative body image. The description of the relationship between knowledge of balanced nutrition does not really affect the perception of body image. It is shown that the sample who has sufficient and good knowledge is still dominant in having a negative body image perception.